Model Kolaborasi Chatbot dan Manusia dengan Mekanisme Handoff berbasis Trigger untuk Optimalisasi Layanan Pelanggan UMKM di Era Digital - Dimas Adi Wicaksono; Heru Yulianto; Aji Priyambodo (Dinamik, 2026)
The development of artificial intelligence (AI) technology has changed the paradigm of customer service by introducing Chatbots as a solution to improve service efficiency and availability. However, in the context of micro, small, and medium enterprises (MSMEs), limited resources and the complexity of customer interactions require a hybrid approach that integrates Chatbots with human agents. This study designed a model for collaboration between Chatbots and humans with a trigger-based handoff mechanism that enables automatic transitions based on measurable indicators, such as negative sentiment, complex questions, and explicit customer requests. Using a simulation approach on 5,000 customer conversations, this study found that the hybrid model was able to increase the Customer Satisfaction Score (CSAT) from 3.6 to 4.2, reduce completion time from 6.2 minutes to 3.8 minutes, and increase customer loyalty from 52% to 68%. The implementation roadmap is structured in three levels (beginner, intermediate, advanced) to suit the varying digital capabilities of SMEs. This research contributes to the literature on human-AI collaboration and omnichannel customer experience, and offers an applicable framework for SMEs to accelerate the digital transformation of customer service.